Involvement of diacylglycerol production in activation of nuclear factor kappaB by a CD14-mediated lipopolysaccharide stimulus. - Yamamoto, H (1997)
Exposure of Chinese hamster CHO-K1 transfectant cells expressing mouse CD14 (CHO/CD14 cells) to lipopolysaccharide (LPS) induced rapid elevation of the cellular diacylglycerol (DAG) and choline/phosphocholine levels and nuclear translocation of nuclear factor kappaB (NFkappaB). When cells were incubated with short-chain DAG analogues or bacterial phospholipase C, NFkappaB activation occurred even without the LPS stimulus. Treatment of CHO/CD14 cells with tricyclo[5.2.1.0(2.6)]decyl-(9[8])xanthogenate (D609), an inhibitor of phosphatidylcholine-specific phospholipase C and phospholipase D, almost completely inhibited not only the LPS-dependent production of DAG and choline/phosphocholine but also the LPS-dependent NFkappaB activation. In contrast, treatment of cells with 1-(6-¿[3-methoxyoestra-1,3, 5(10)-trien-17beta-yl]-1H-pyrrole-2,5-dione (U73122), an inhibitor of phosphatidylinositol-specific phospholipase C in vitro, did not affect the LPS-dependent activation of NFkappaB. Production of DAG and activation of NFkappaB after the LPS stimulus were observed in mouse macrophage-like J774.1 cells, and this response to LPS by J774. 1 cells was also inhibited by D609. These results suggest that the production of DAG from phosphatidylcholine was upstream of NFkappaB activation in response to a CD14-mediated LPS stimulus.